(untitled) (Świat Idei i Polityki, 2014)
The main aim of the article is the analysis of the development of Swiss political system. The analysis starts on September 1:t, 1291, when the three cantons Uri, Schwyz, and Nidwalden created the alliance (Fidgenossenchaft), and takes under considerations all important events that happened on the Swiss path to contemporary political system. The considerations are made from the historical perspective.